Pretreatment with Sodium Phenylbutyrate Alleviates Cerebral Ischemia/Reperfusion Injury by Upregulating DJ-1 Protein - Yang, Rui-Xin (Front Neurol, 2017)
Oxidative stress and mitochondrial dysfunction play critical roles in ischemia/reperfusion (I/R) injury. DJ-1 is an endogenous antioxidant that attenuates oxidative stress and maintains mitochondrial function, likely acting as a protector of I/R injury. In the present study, we explored the protective effect of a possible DJ-1 agonist, sodium phenylbutyrate (SPB), against I/R injury by protecting mitochondrial dysfunction via the upregulation of DJ-1 protein. Pretreatment with SPB upregulated the DJ-1 protein level and rescued the I/R injury-induced DJ-1 decrease about 50% both in vivo and in vitro. SPB also improved cellular viability and mitochondrial function and alleviated neuronal apoptosis both in cell and animal models; these effects of SPB were abolished by DJ-1 knockdown with siRNA. Furthermore, SPB improved the survival rate about 20% and neurological functions, as well as reduced about 50% of the infarct volume and brain edema, of middle cerebral artery occlusion mice 23 h after reperfusion. Therefore, our findings demonstrate that preconditioning of SPB possesses a neuroprotective effect against cerebral I/R injury by protecting mitochondrial function dependent on the DJ-1 upregulation, suggesting that DJ-1 is a potential therapeutic target for clinical ischemic stroke.